UNCITRAL Technical Notes on Online Dispute Resolution as Soft Law Instrument for Online Dispute Resolution: An Indonesia Perspective - Budhijanto, Danrivanto; Roosdiono, Anangga W.; Maulana, Mursal (BANI Arbitration and Law Journal, 2025)
This article discusses the UNCITRAL Technical Notes on Online Dispute Resolution, a soft law instrument designed by UNCITRAL. The Notes are non-binding instrument in nature, descriptive, and could be used as procedural rules governing online dispute resolution (ODR). With the rise of e-commerce, ODR can be considered an effective and efficient mechanism for resolving disputes arising from cross-border transactions worldwide, including in Indonesia. To ensure optimal implementation of ODR, a legal framework governing the online dispute resolution process is essential. To date, most countries and ODR institutions still lack substantive and procedural rules regarding ODR. The emergence of the UNCITRAL Technical Notes on Online Dispute Resolution is considered to be potential option, notwithstanding its purely soft law character. While not legally binding, disputing parties can consensually agree to use the Notes as rules of procedure.This article is structured in four parts. The first part is an introduction that briefly discusses the existence of ODR in last recent decades as a consequence of the rise in e-commerce activity. The second part discusses the history of ODR and recent developments in several jurisdictions. The third section discusses the scope of the UNCITRAL Technical Notes on Online Dispute Resolution and the final section as a conclusion proposes that Soft Law instruments such as the UNCITRAL Technical Notes on Online Dispute Resolution can function as instruments that can be used as alternative sources of ODR law.